Why do hospital prescribers continue antibiotics when it is safe to stop? Results of a choice experiment survey - Roope, L; Buchanan, J; Morrell, L; Pouwels, K; Sivyer, K; Mowbray, F; Abel, L; Cross, L; Yardley, L; Peto, T; Walker, A; Llewelyn, M; et al. (BioMed Central, 2020)
Background: Deciding whether to discontinue antibiotics at early review is a cornerstone of hospital antimicrobial stewardship practice worldwide. In England, this approach is described in government guidance (‘Start Smart then Focus’). However, < 10% of hospital antibiotic prescriptions are discontinued at review, despite evidence that 20–30% could be discontinued safely. We aimed to quantify the relative importance of factors influencing prescriber decision-making at review.